MASTOID OSTEOMA OF THE TEMPORAL BONE - Bundovska, Smiljana; Belceska, Gordana Antuleska; Spirov, Goran (Journal of Morphological Sciences; Vol 4 No 2 (2021): JMS, 2021)
Osteomas are osteoblastic neoplasms affecting the parietal and frontal bone.  Mastoid osteomas of temporal bone are rare benign tumors with incidence of 0.1%-1% of all benign tumors of the skull.We present a case of a young 19-year-old female who complained of right posterior auricular hard swelling which had gradually increased in size over the past 2 years and felt pain for less than a year.There was no history of trauma, symptoms of inflammation or occlusion of the ear canal. She felt a pain during the eruption of her second molar teeth. Non-contrast CT was done and it showed a well-defined densely calcified lesion of bone attenuation in the right mastoid posteriorly measuring 1.7 Ã— 1 Ã— 2.3 cm. The middle ear cavity, ossicular chain, inner table of skull and diploe were normal with no extension intracranially and no bony destruction. These findings spoke in favor of a mastoid osteoma. Key words : osteoma, temporal bone, ear https://doi.org/10.55302/JMS2142054bk